On the potential of the lagrangian estimator for endovascular ultrasound elastography: in vivo human coronary artery study - Maurice, Roch L; Fromageau, Jérémie; Brusseau, Elisabeth; Finet, Gérard; Rioufol, Gilles; Cloutier, Guy (Ultrasound in medicine & biology, 2007)
Diagnosis and prognosis of coronary artery atherosclerosis evolution currently rely on plaque morphology and vessel stenosis degree. Such information can accurately be assessed with intravascular ultrasound (IVUS) imaging. A severe complication of coronary artery atherosclerosis is thrombosis, a consequence of plaque rupture or fissure, which might lead to myocardial infarction and sudden ischemic death. Plaque rupture is a complicated mechanical process, correlated with the plaque morphology, composition, mechanical properties and with the blood pressure. Extracting information on the plaque local mechanical properties may reveal relevant features about plaque vulnerability. Accordingly, endovascular elastography (EVE) was introduced to complement IVUS for investigating coronary artery diseases. In this article, in vivo elastographic data are reported for three patients (patient 1, patient 2 and patient 3) who were diagnosed with severe coronary artery stenoses. Time-sequence radio-frequency (RF) data were acquired, in the minutes preceding angioplasty, using an ultrasound scanner working with a 30 MHz mechanical rotating single-element transducer. The elastograms of the radial strain and radial shear distributions within the vessel wall were computed from pairs of successive RF images using the Lagrangian estimator (LE). A hard atherosclerotic plaque (low radial strain and shear) was identified in patient 1. High radial strain and shear values in the plaque areas for patient 2 and patient 3 suggested the presence of lipid cores (soft materials), known to be prone-to-rupture sites when located close to the lumen. To conclude, EVE allowing radial strain and shear images is an improvement over existing EVE methods that may assist IVUS in preoperative vessel lesion assessments and in endovascular therapy planning.